The philosophical assumptions of theological research (biblical and systematic) - Turpo Chaparro, Joel (2017)
This research examines Greek philosophical categories influence on theology. This will do through the historical-critical method of biblical theology and in the reality conception of the theological system. In this sense, it is argued that both conception of God's being, reality, doctrines and the nature of man have incurred several biblical-theological errors because of Greek philosophical framework influence that has penetrated strongly in the method to do biblical theology, that is to say in exegesis and in the presuppositions for elaboration of a systematic theology.